Molecular forms of neurogranin in cerebrospinal fluid. Issue 3 (17th December 2020) - Nazir, Faisal Hayat; Camporesi, Elena; Brinkmalm, Gunnar; Lashley, Tammaryn; Toomey, Christina E.; Kvartsberg, Hlin; Zetterberg, Henrik; Blennow, Kaj; Becker, Bruno
Abstract: Neurogranin (Ng) is a 78 amino acid neuronal protein and a biomarker candidate for Alzheimer's disease (AD). Ng has been suggested to bind to calmodulin and phosphatidic acid via its centrally located IQ domain. Ng is cleaved within this functionally important domain, yielding the majority of fragments identified in cerebrospinal fluid (CSF), suggesting that cleavage of Ng may be a mechanism to regulate its function. Up to now, Ng has been shown to be present in CSF as both C‐terminal fragments as well as full‐length protein. To obtain an overview of the different molecular forms of Ng present in CSF, we show by size exclusion chromatography (SEC), immunoblotting, immunoprecipitation, and MS that Ng is present in CSF as several molecular forms. Besides monomeric full‐length Ng, also higher molecular weight forms of Ng, and C‐terminal‐ and previously not identified N‐terminal fragments were observed. We found by immunodepletion that C‐terminal peptides contribute on average to 50% of the total‐Ng ELISA signal in CSF samples. There were no differences in the overall C‐terminal fragment/total‐Ng ratios between samples from AD and control groups. In addition, we found that monomeric Ng and its C‐terminal fragments bind to heparin via a heparin‐binding motif, which might be of relevance for their export mechanism from neurons. Taken together, this study highlights the presence of several molecular forms of Ng in CSF, comprising monomeric full‐length Ng, and N‐ and C‐terminal truncations of Ng, as well as larger forms of still unknown composition. Abstract : C‐terminal fragments, along with full‐length forms of neurogranin (Ng) have been previously found at higher concentration in CSF from Alzheimer´s disease patients. Calpain 1 cleaves Ng in its IQ domain upon activation by Ca ions. This IQ domain is essential for modulating calmodulin and CaMKII signaling toward LTP. Using SEC, western blotting, and IP‐MS, we show that N‐terminal Ng and high molecular weight forms of Ng can be also be found in CSF. These Ng forms may have physiologic relevance and be of importance for the understanding of pathologic processes in brain disorders and for the development of specific biomarker assays.